A Determinants Model of Employee Productivity: The Roles of Discipline, Organizational Citizenship Behavior, Quality of Work Life, Employee Commitment, and Job Satisfaction with Motivation as a Mediator and Compensation as a Moderator - Rhifwan Aji Bimantoro Adriyanto; Hapzi Ali (Dinasti Publisher, 2026)
This study is a literature review that examines the determinants model of employee productivity by considering the role of work discipline, Organizational Citizenship Behaviour (OCB), Quality of Work Life (QWL), employee commitment, and job satisfaction as exogenous variables, motivation as a mediating variable, and compensation as a moderating variable. The purpose of this article is to build testable hypotheses for subsequent empirical research. The research method employs library research and Systematic Literature Review (SLR), with qualitative descriptive analysis sourced from e-books and open-access e-journals with international reputation (Sinta 1 and Scopus Q2). The results of this review indicate that: 1) work discipline affects employee productivity; 2) OCB affects employee productivity; 3) QWL affects employee productivity; 4) employee commitment affects employee productivity; 5) job satisfaction affects employee productivity; 6) motivation mediates the influence of exogenous variables on employee productivity; and 7) compensation moderates the relationship between motivation and employee productivity